Effect of cooling strategy on the bearing capacity of CF/PEEK composite hole. (1st February 2023) - Qi, Zhenchao; Xu, Zhichao; Li, Fengchen; Yao, Chenxi
Abstract: Currently, carbon fibre-reinforced polyetheretherketone (CF/PEEK) hole-making process employs the same fast cooling strategy as in a traditional thermosetting composite to avoid hole wall burns. However, owing to the characteristics of thermoplastic resins, excessive cooling adversely affects the recrystallisation process of PEEK resins in the high-temperature region. This poses questions against the conventional perception that "cooling is beneficial." To address this issue, mechanical parameters of the samples treated at different cooling rates were measured. The mechanical response and material damage of the holes under load were analysed, and the relationship between material cooling rate, crystallinity, and mechanical properties was established. A retarded cooling strategy was proposed to actively control the temperature after the hole-making. The effects of fast cooling, natural cooling, and retarded cooling on the quality of CF/PEEK holes were analysed by differential scanning calorimetry (DSC), tensile, and fatigue tests, and the detrimental effect of fast cooling on the quality of the hole structure was confirmed. The results reveal that compared with fast cooling, the ultimate tensile strength of the retarded cooling components is increased by 23.64%, and the fatigue life is increased by more than 10 times at 65% σult. The retarded cooling strategy improved the quality of CF/PEEK holes.